Silver nanoparticle based highly selective and sensitive solvatochromatic sensor for colorimetric detection of 1, 4-dioxane in aqueous media. Issue 88 (17th September 2015) - Kumar, Anshu; Vyas, Gaurav; Bhatt, Madhuri; Bhatt, Shreya; Paul, Parimal
Abstract : A silver nanoparticle based solvatochromic sensor that selectively and sensitively detects 1, 4-dioxane in aqueous media has been developed. The nanoparticle surfaces generate ROS, which promote 1, 4-dioxane degradation, causing a sharp colour change. Abstract : A citrate stabilised silver nanoparticle (Ci-AgNP) based solvatochromic sensor, which functions as a highly selective and sensitive colorimetric probe for 1, 4-dioxane in aqueous media is reported. The surfaces of the AgNPs generate reactive oxygen species, which promote the degradation of 1, 4-dioxane assembled in the vicinity of the nanoparticle surfaces through charge transfer interactions. During this process, Ag 0 is oxidised to Ag + and the yellow colour of the solution turns to colourless. The sensor was used for the estimation of 1, 4-dioxane in ground water and also 1, 4-dioxane vapour diffused in aqueous media.